A case report of Management of impaction colic in Donkey in Ibadan, Nigeria (2020)
Ram fighting is one of the unimaginable sports practiced all around the World. It is often associated with all sorts of injuries which may predispose animals to tetanus. Tetanus is an acute, severe and potentially fatal toxin-mediated disease caused by Clostridium tetani infection. This organism thrives under anaerobic conditions, such as unclean environment, contaminated wounds. A case of an adult West African Dwarf Ram, weighing 45kg presented with generalized stiffness, mild opistotonus, difficulty in swallowing and signs of generalized pain was presented. On physical examination, rapid breathing and mild bloat were observed, but every other clinical parameter was within the normal reference values. Tentative diagnosis of tetanus associated with injuries sustained during animal figthing. The patient was treated with human tetanus immunoglobulin followed by intravenous metronidazole, procaine penicillin streptomycin and diazepam injection administered intramuscularly. High dose of multivitamins was administered I/M. The symptoms were relieved after three hours of intensive treatment each day for two consecutive days. The client failed to present the patient to the clinic for follow-up on the third day citing cost and distance to the clinic as excuses. To the authors’ knowledge a tetanus infection associated with injury from Ram fight has not been previously reported in Ibadan, Nigeria.